Individual factors that influence knowledge sharing intention among bank employees in Northern Region of Malaysia - Saravanan, Nadason (2019)
The primary aim of this study was to observe whether attitude, subjective norms, perceived behavioural influenced knowledge sharing intention. This study was based on Theory of Planned Behaviour (TPB) to explain the relation between attitude, subjective norms, perceived behavioural control and intention. KS intention is important because it will determine the success of KS behaviour. A total of 136 bank employees from Perlis, Kedah and Penang participated in this study. Data was gathered through self-administered questionnaires and the collected data was analysed using SPSS software version 20 to test the hypothesis. The findings revealed that only subjective norms positively related to knowledge sharing intention. Finally, the practical and theoretical implications alongside the recommendations for future research were discussed.